ANALISIS PENGEMBANGAN FASILITAS PELABUHAN PERIKANAN LAMBADA LHOK KABUPATEN ACEH BESAR - Miftahul Rizqi; Muklis; Kurnia; Faisal Syahputra (JURNAL KREASI RAKYAT, 2025)
PP Lambada Lhok is one of the most strategic ports in Aceh, located adjacent to the port of Malahayati, PP Lambada Lhok is directly facing WPP 571 and WPP 572, namely the Strait of Malacca and the Indian Ocean. Despite its strategic location, initial observations of PP Lambada Lhok showed that there were deficiencies in facilities that hindered smooth operations, such as the shallowness of the pond which made it difficult for fishing boats to enter and exit and even potentially paralyzed port operations. In addition, the mooring place is not suitable at the dock and there is a TPI other than PP Lambada Lhok. This research aims to see the existing facilities at Lambada Lhok Fishery Port, Aceh Besar Regency, Aceh Province. The results of the research Lambada Lhok fishing port once had the status of a Fish Landing Base (PPI). However, PP Lambada Lhok facilities such as the fish unloading dock, the depth of the port pond and the Fish Auction Place (TPI) need to be improved so that activities at PP Lambada Lhok run normally.